Effects of human TFPI and CD47 expression and selectin and integrin inhibition during GalTKO.hCD46 pig lung perfusion with human blood. (2nd March 2022) - Miura, Shuhei; Habibabady, Zahra A.; Pollok, Franziska; Connolly, Margaret; Pratts, Shannon; Dandro, Amy; Sorrells, Lori; Karavi, Kasinath; Phelps, Carol; Eyestone, Will; Ayares, David; Burdorf, Lars; et al.
Abstract: Background: Loss of barrier function when GalTKO.hCD46 porcine lungs are perfused with human blood is associated with coagulation pathway dysregulation, innate immune system activation, and rapid sequestration of human formed blood elements. Here, we evaluate whether genetic expression of human tissue factor pathway inhibitor (hTFPI) and human CD47 (hCD47), alone or with combined selectin and integrin adhesion pathway inhibitors, delays GalTKO.hCD46 porcine lung injury or modulates neutrophil and platelet sequestration. Methods: In a well‐established paired ex vivo lung perfusion model, GalTKO.hCD46.hTFPI.hCD47 transgenic porcine lungs (hTFPI.hCD47, n  = 7) were compared to GalTKO.hCD46 lungs (reference, n  = 5). All lung donor pigs were treated with a thromboxane synthase inhibitor, anti‐histamine, and anti‐GPIb integrin‐blocking Fab, and were pre‐treated with Desmopressin. In both genotypes, one lung of each pair was additionally treated with PSGL‐1 and GMI‐1271 (P‐ and E‐selectin) and IB4 (CD11b/18 integrin) adhesion inhibitors ( n  = 6 hTFPI.hCD47, n  = 3 reference). Results: All except for two reference lungs did not fail within 480 min when experiments were electively terminated. Selectin and integrin adhesion inhibitors moderately attenuated initial pulmonary vascular resistance (PVR) elevation in hTFPI.hCD47 lungs. Neutrophil sequestration was significantly delayed during the early time points following reperfusion and terminal platelet activation was attenuated in association with lungs expressing hTFPI.hCD47, but additional adhesion pathway inhibitors did not show further effects with either lung genotype. Conclusion: Expression of hTFPI.hCD47 on porcine lung may be useful as part of an integrated strategy to prevent neutrophil adhesion and platelet activation that are associated with xenograft injury. Additionally, targeting canonical selectin and integrin adhesion pathways reduced PVR elevation associated with hTFPI.hCD47 expression, but did not significantly attenuate neutrophil or platelet sequestration. We conclude that other adhesive mechanisms mediate the residual sequestration of human formed blood elements to pig endothelium that occurs even in the context of the multiple genetic modifications and drug treatments tested here.